Descripcion del manejo y aprovechamiento productivo que se obtiene de la captura y esquila de vicuñas (vicugnavicugna) vivas en el caserio de cushuro-huamachuco - Cribilleros Ríos, Raúl Jesus (2015)
Through this research it has been able to determinate how to processof capture and shearing of vicunas is made; the economic losses caused by poor capture and shearing, and finally it has managed plating to improve the process of capture and shearing of vicuñas in this herd of vicunas of the Association of Small Farmers “Futuro y Desarrollo” Village of Cushuro, district of Huamachuco, Sánchez Carrión Province, Region La Libertad. We caught a total of 321 vicunas (73 very young´s, 71 young’s and 177 adults); that is to say 68% of vicunas exists in this herd of vicuñas. It has a total of 126 sheared vicunas of which are 60 youth and 66 adults. It has obtained a total of 126 fleeces with a gross weight of 21,821 kg fiber. There a total of 195 shearedvicunas of which were 73 pups, 11 youth and 111 adults. The results were analyzed by the way how are you two activities capture and shearing of live vicuñas were made. Concluding that the capture and shearing of vicuñas for productive purposes in this herd had a 68% efficiency.